Strategic human resource management - Anthony, William P. (Dryden P. OrlandoUS, 1993)
Examines typical functions in personnel management, such as recruitment, selection, training, rewarding (wage and salary analysis), from a strategic perspective. Explores how these functions integrate with the overall strategy of the firm, in order for the firm to become more competitive.